2021 IEEE 7th International Conference on Network Softwarization (NetSoft) 2021
DOI: 10.1109/netsoft51509.2021.9492679
|View full text |Cite
|
Sign up to set email alerts
|

SDN Intent-based conformance checking: application to security policies

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Such automation not only ensures optimal performance but also promotes security by tailoring connections to specific needs, reducing potential vulnerabilities or mismatches. In [15], it is shown that intents can also be used for faster security policy conformance checking. The time to verify the host connection permissions is significantly reduced by using algorithms that process intent lists that detail host connections.…”
Section: B Automated Security Configurationmentioning
confidence: 99%
“…Such automation not only ensures optimal performance but also promotes security by tailoring connections to specific needs, reducing potential vulnerabilities or mismatches. In [15], it is shown that intents can also be used for faster security policy conformance checking. The time to verify the host connection permissions is significantly reduced by using algorithms that process intent lists that detail host connections.…”
Section: B Automated Security Configurationmentioning
confidence: 99%